(untitled) (diségno, 2023)
In the Metamorphoses, Ovid recounts the myth of the labyrinth, the story of Daedalus and Icarus and the overcoming through flight of the labyrinthine structure, a symbol of imprisonment but also of the indissoluble bond between one’s body and one’s view of the world. [read more]